(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The scientific article talks about culture as a continuous conscious creative activity, which is associated with the creation of material and spiritual riches, their preservation and transmission to future generations. The process of emergence and development of reading culture as a structural, important element of general culture is considered. It is explained that it is a set of special knowledge, skills and experience necessary to study publications and electronic resources, and recommendations are given on the formation of reading culture in cooperation of family, school and library.